Analisis Kelayakan Bisnis Minuman Es Teh Ditinjau dari Prinsip Ekonomi Syariah : Studi Kasus Kedai FreshTea di Jl.Hidayatullah Kec. Sangatta Utara - Mutmainnah Mutmainnah; Arif Rembang Supu; Muhammad Imam Syafi’i (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
In general, this research aims to assess the business feasibility of iced tea beverages at FreshTea Cafe based on aspects of business feasibility and principles of Islamic economics. This assessment includes an evaluation of the extent to which the business meets feasibility criteria from the perspectives of market, legal, location and environment, human resources, technical and production, as well as financial aspects, while also assessing its alignment with the principles of Islamic economics. Meanwhile, the specific objectives of this research are to analyze the business feasibility of iced tea beverages at FreshTea Cafe based on these aspects of business feasibility, and to evaluate the compatibility of the business practices carried out with the principles of Islamic economics in order to ensure the sustainability of halal, ethical, and competitive enterprises. Based on the research results, it shows that the iced tea business at FreshTea Cafe is feasible to run and develop based on the analysis of business feasibility aspects, such as market demand, legal aspects, location and environment, human resources, technical production, and finance. Stable market demand, a strategic location, effective promotion, and good business management support the sustainability of the business. Financial management is conducted transparently, and human resources are selected with an emphasis on honesty and responsibility. In addition, FreshTea Cafe has implemented the principles of Islamic economics, such as justice, balance, public welfare, monotheism, prohibition of usury, zakat, infaq, charity, waqf, cooperation, and oversight (hisbah). These values are reflected in daily business practices and have a positive impact on customer loyalty and the blessings of the business. Thus, FreshTea is deemed suitable and has the potential as a sustainable iced tea business in line with the principles of Islamic economics.